2015
DOI: 10.1051/0004-6361/201526343
|View full text |Cite
|
Sign up to set email alerts
|

The protoMIRAX hard X-ray imaging balloon experiment

Abstract: Context. The protoMIRAX hard X-ray imaging telescope is a balloon-borne experiment developed as a pathfinder for the MIRAX satellite mission. The experiment consists essentially in a coded-aperture hard X-ray (30-200 keV) imager with a square array (13 × 13) of 2 mm-thick planar CZT detectors with a total area of 169 cm 2 . The total, fully-coded field-of-view is 21 • × 21 • and the angular resolution is 1 • 43 . Aims. The main objective of protoMIRAX is to carry out imaging spectroscopy of selected bright sou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…This problem refers to real-time TeleMetry (TM) data transmission from a hard X-ray imaging telescope which is to be launched by a balloon and will operate between 40 to 42 km of altitude [57,58]. The On-Board Data Handling Subsystem (OBDH) is responsible for acquiring, formatting, and transmitting to the Ground Station (GS) all TM data generated by several subsystems (X-ray Camera (XRC), Attitude Control Subsystem (ACS)) of the space segment.…”
Section: Space Applications Communication Problemmentioning
confidence: 99%
“…This problem refers to real-time TeleMetry (TM) data transmission from a hard X-ray imaging telescope which is to be launched by a balloon and will operate between 40 to 42 km of altitude [57,58]. The On-Board Data Handling Subsystem (OBDH) is responsible for acquiring, formatting, and transmitting to the Ground Station (GS) all TM data generated by several subsystems (X-ray Camera (XRC), Attitude Control Subsystem (ACS)) of the space segment.…”
Section: Space Applications Communication Problemmentioning
confidence: 99%
“…The peak on the right is produced by a fixed-height pulser for peak width comparison. Taken from Braga et al (2015).…”
Section: The Detector Systemmentioning
confidence: 99%
“…In order to predict the performance of LECX for observations of GRBs and related phenomena, we have carried out a series of Monte Carlo simulations taking into account typical GRB spectra and the predicted LECX background. Since the LECX's graded shield, which is the same as the one used in our balloon project protoMI-RAX (Braga et al 2015), has been shown by Castro et al (2016) to be very effective in absorbing most gamma-rays in the typical GRB energy ranges, and also in cutting off the lead and tin fluorescence, we do not expect to have any significant contribution of scattering and transmission of the burst photons in the collimator. We also expect that contamination from GRB photons scattering off the spacecraft structure will be negligible since there is very little material in the cubesat platform and the detector plane is well shielded from below.…”
Section: Simulations Of Cosmic Explosion Detectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The balloon version of the instrument is called protoMI-RAX (Braga et al 2015) and will be launched for the first time from Cachoeira Paulista, SP, Brazil, in late 2016 for a ∼ 24-hour flight. The balloon flight will test several MIRAX subsystems in a near-space environment and will carry out imaging demonstrations of the camera by observing bright X-ray sources.…”
Section: Introductionmentioning
confidence: 99%